2020
DOI: 10.1111/odi.13269
|View full text |Cite
|
Sign up to set email alerts
|

Intraepithelial CD163+ macrophages in tongue leukoplakia biopsy: A promising tool for cancer screening

Abstract: Objective Oral leukoplakia has mixed and differing histopathological features, and it is thus difficult to reach an accurate histological diagnosis of oral leukoplakia based on a local biopsy alone. We recently demonstrated the significance of CD163+ macrophages in oral carcinogenesis. Herein we sought to determine whether CD163+ macrophages in biopsy specimens of oral leukoplakia help identify the overall histological nature of the lesion. Patients and Methods Twenty‐six patients with tongue leukoplakia who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…On the other hand, studies have reported a few rare cases of OVX associated with malignant lesions [36][37][38]. In addition, several investigators have reported about the correlation between CD163 + macrophages and epithelial dysplasia and the malignancy of oral precancerous lesions [13,14,39,40]. Therefore, we must not overlook the malignant potential of squamous epithelium within the OVXs, which are considered as benign reactive lesions.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, studies have reported a few rare cases of OVX associated with malignant lesions [36][37][38]. In addition, several investigators have reported about the correlation between CD163 + macrophages and epithelial dysplasia and the malignancy of oral precancerous lesions [13,14,39,40]. Therefore, we must not overlook the malignant potential of squamous epithelium within the OVXs, which are considered as benign reactive lesions.…”
Section: Discussionmentioning
confidence: 98%
“…We previously proposed that tongue leukoplakia biopsy, with an intraepithelial lesion in which intraepithelial CD163 + cells are observed, may suggest that invasive cancer is present in the neighborhood of the specimen [ 9 ]. We herein sought to determine whether CD163 + macrophages provide a hint for the evaluation of malignant potency of OLC.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, whether this patient had invasive cancers initially, or the malignant transformation occurred after the first biopsy, must be carefully discussed. Previously, we demonstrated CD163 + macrophages were infiltrated in the stromal area, but not in the intraepithelial area of nonneoplastic lesions including OLP, oral candidiasis and aphthous stomatitis [ 9 ]. Our findings, overall, indicate that OLC in this study had a high malignant potency, and the small number of intraepithelial CD163 + macrophages observed in the first biopsy specimen should not be overlooked.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations